2011
DOI: 10.1139/f2011-053
|View full text |Cite
|
Sign up to set email alerts
|

Home range of European lobster (Homarus gammarus) in a marine reserve: implications for future reserve design

Abstract: Marine reserves are perceived as a critical component in successful rebuilding of overharvested marine populations. Such efforts can be particularly successful in species with limited movement rates. However, long-term data on movement is sparse for most marine species. Here, we investigated space use in European lobster ( Homarus gammarus ) by ultrasonic tracking in a reserve on the Norwegian Skagerrak coast from September 2006 to August 2007. Over the period, 95% of tagged lobsters remained either within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 62 publications
6
84
1
5
Order By: Relevance
“…Espinoza et al 2011, Moland et al 2011. Our study illustrates that VPS is well suited to studies of slowmoving species such as queen conch, providing long-term movement paths on spatial resolution of usually better than 15 m, and allowing the calculation of home ranges on correspondingly small spatial scale and resolution.…”
Section: High-resolution Acoustic Telemetry Of Slow-moving Animalsmentioning
confidence: 77%
“…Espinoza et al 2011, Moland et al 2011. Our study illustrates that VPS is well suited to studies of slowmoving species such as queen conch, providing long-term movement paths on spatial resolution of usually better than 15 m, and allowing the calculation of home ranges on correspondingly small spatial scale and resolution.…”
Section: High-resolution Acoustic Telemetry Of Slow-moving Animalsmentioning
confidence: 77%
“…Evidence also indicated a 'spillover' into areas adjacent to the NTZ where an increase of sub-legal lobsters was observed (Hoskin et al 2011). In contrast, European lobster tagged in a Skagerrak coast reserve (Norway) were observed to remain in the reserve or near the boundary (Moland et al 2011).…”
Section: Conservation and Protected Areasmentioning
confidence: 92%
“…may depend on their size, sex and specific behavioural patterns (foraging, moulting, mating, dominance and territorial behaviour) (Branford 1979;Lawton 1987;Karavanich & Atema 1998;Mehrtens et al 2008;Schmalenbach et al 2011). So far, field studies that quantified movement in adult lobsters reported no significant differences in home ranges between lobster size and sex (Scopel et al 2009;Moland et al 2011b).…”
Section: Introductionmentioning
confidence: 99%